Resumes, cover letters & interviewing setting the stage for success - Eischen, Clifford W (South-Western College Publishing, 2000)
This practical, how-to resume manual guides you through the process of crafting a polished, professional resume using today's business technologies including the Internet and E-mail. It is specifically written for individuals with two-year degrees to showcase their skills and experiences in order to get the job they want.